Analisis Faktor-Faktor Yang Mempengaruhi Pergantian Auditor (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di BEI tahun 2011-2014) - Cholil, Annisa; , Dra. Nursiam, M.H., Ak., CA (2016)
The purposes of this research are to analyze the influence of management exchange, leverage, and size of public accountant firm toward auditor switching. The population in this research are the manufacture companies listed in Indonesia Stock Exchange for year of 2011-2014 which consist of 153 companies. The sampling technique is a purposive sampling method which results for 33 samples. The data analysis method uses descriptive statistic analysis and logistic regression analysis. The result of this study shows that the following variables management exchange, and the size of public accountant firm affect toward auditor switching. On the other hand, leverage don't affect toward auditor switching.This means that auditor switching affected by the change of management and size of public accountant. Keywords:auditor switching, management exchange, leverage, and size of public accountant.